When to conduct a vocabulary quiz, before the review or after the review?. (December 2021) - Kasahara, Kiwamu; Kanayama, Kohei
Abstract: The purpose of this study is to find the optimal timing for giving learners a small quiz for L2 vocabulary learning. This study had 68 university students remember 20 English and Japanese word pairs. A week later, the S-TS group ( n = 30) took the first L1 meaning recall test before the review, whereas the S-ST group ( n = 38) took the review before the recall test. Both groups took Posttest 1 a week later and Posttest 2 a month later. The S-TS group showed a higher retention rate in Posttest 1 and the gap became larger in Posttest 2. The present study provided original Results in that (a) it showed the positive effects of a test session before the review on long-term retention; (b) it took into consideration the effect of participants' expectations of Posttest 1 on the test results; (c) it revealed that higher expectations of a subsequent test by the S-TS group may have led to better performance in the test.